The Influence of Learning Environment on Student Achievement of Islamic Relegious Education Subjects at Shodiqussalam Vocational School Central Lampung - Sulis Wahyuningsih; Muhammad Kharis Fadillah (Journal of Research in Islamic Education, 2022)
This research is motivated by a learning environment that is realized to play a role in the learning process, one of which is Islamic Religious Education. The learning environment which is classified as a social and non-social environment still does not encourage an increase in PAI learning achievement. Writing this thesis aims to determine the influence of the social environment and the non-social environment either individually or jointly on PAI learning achievement. This study uses a quantitative approach, the analysis uses simple and multiple linear regression statistics. The population is 40 students consisting of students in class X, X1 and XII SMK IT Shodiqussalam, the variables in this study include the social environment,non-social environment and PAI learning achievement. Data collection using questionnaires and documentation. The results of the study obtained the first equation Y=47.665+0.430,with a significance value of 0.899. The second equation Y=41.327+0.480 with a significance value of 0.944. The third equation Y=38.791+0.608X1+0.979X2 with a significance value of 0.608. These results indicate the influence of the social environment on PAI learning achievement and the influence of the non-social environment on PAI learning achievement and together have an influence on PAI achievement at SMK IT Shodiqussalam.The conclusions in this study are (1) the higher the social environment, the higher the learning achievement; (2) the higher the non-social environment will result in higher learning achievement; and (3) the higher the social and non-social environment, the higher the learning achievement.